2016
DOI: 10.1016/j.appet.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviour associated with differences in conflict adaptation for food pictures

Abstract: Objective: The goal conflict model of eating (Stroebe, Mensink, Aarts, Schut, & Kruglanski, ( 2008) proposes differences in eating behaviour result from peoples’ experience of holding conflicting goals of eating enjoyment and weight maintenance. However, little is understood about the relationship between eating behaviour and the cognitive processes involved in conflict. This study aims to investigate associations between eating behaviour traits and cognitive conflict processes, specifically the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…This measure has been extensively validated and demonstrated both reliability and consistency within general and clinical populations (Caccialanza et al, 2004;Wardle, 1987). Further, it has previously been used in research examining restraint and cognitive performance (Husted, Banks & Seiss, 2016;Shaw & Tiggemann, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…This measure has been extensively validated and demonstrated both reliability and consistency within general and clinical populations (Caccialanza et al, 2004;Wardle, 1987). Further, it has previously been used in research examining restraint and cognitive performance (Husted, Banks & Seiss, 2016;Shaw & Tiggemann, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The flanker task procedures were programmed using E-Prime 2.0. The flanker task comes from prior food flanker studies (Forestell et al, 2012; Meule et al, 2012; Husted et al, 2016). In the food flanker task, the central targets were pictures of either high-calorie foods or low-calorie foods images, which were flanked by pictures either from the same category (congruent condition) or distractors from the other category (incongruent condition).…”
Section: Methodsmentioning
confidence: 99%
“…This “flanker effect” phenomenon, that is, slower responses to incongruent trials, provides an index of the conflict monitoring. Due to the lower levels of cognitive control being successfully applied, the flanker effect will be larger, which indicates a greater conflict monitoring deficit (Husted et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies demonstrated an attentional bias to food among those who are high on EE, others showed attentional avoidance or did not show any difference in attention to food among individuals who are high versus low on EE [12]. For example, Husted et al [16] reported that higher levels of EE were related to slower responses to food pictures, indicating a food-target avoidance according to the authors. In contrast, another study showed increased attentional capture by food cues among women with high versus low levels of EE, as measured using eye-tracking [17].…”
Section: Introductionmentioning
confidence: 96%